Limbah Loom sebagai Alternatif Material Mebel - Susi Hartanto (JURNAL RUPA, 2018)
Furniture factories are one of Cirebon's economy boosters as they employ many workers and produce numerous products for local and export orientation. As a consequence, this industry produces quite a large amount of waste, one of them is paper loom. Loom is a woven paper threads and metal wires which is used to wrap a number of furniture components, such as seat, backrest, etc. Case studies in 2 major factories in Cirebon, total loom waste reaches around 3 tonnes a month. This research provides recommendations of waste usage for furniture.